Norge i polarområdene - Egeland, Knut (Leif Holtedahls forl., 1982)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Petrology and geochemistry of Jurassic basalt dykes from Vestfjella, Dronning Maud Land, Antarctica - Furnes, Herald; Neumann, Else-Ragnhild; Sundvoll, Bjørn (Lithos, 1982)
Mineral and whole rocks analyses of 12 Jurassic basalt dykes from Vestfjella, Dronning Maud Land, Antarctica, are presented, and their genesis discussed. On the basis of major oxides and norms the basalts may be classified as olivine and quartz tholeiites. Plotted in the Plag Cpx (Opx + 4Q) and Ol Plag Q projections, the compositions are most compatible with fractional crystallization of olivine, clinopyroxene and plagioclase from a basalt liquid at very low pressure. The ratios between strongly incompatible elements such as Rb, Cs, Zr, Hf, Ta and Th vary considerably, and petrographic mixing calculations give poor fits with respect to Rb, Cs, Ta, Th and light REE. Initial 87Sr/86 Sr ratios range between 0.70347 and 0.70687, and show no correlation with Rb/Sr or any other SIE ratios. The trace element and Sr isotope data thus do not suggest any simple cogenetic petrogenetic model. It is concluded that the basalt melts most plausibly have been contaminated by, or mixed with anatectic melts of crustal material, rather than reflecting mantle heterogeneity.
Keywords: Dronning Maud Land; geokjemi; geologi; petrologi

Mercury and persistent chlorinated hydrocarbons in antarctic birds from bouvetøya and dronning maud land - Norheim, Gunnar; Sømme, Lauritz; Holt, Gunnar (Environmental Pollution Series A, Ecological and Biological, 1982)
The concentrations of DDE, PCB, hexachlorobenzene (HCB) and mercury were determined in samples from chinstrap penguin Pygoscelis antarctica, macaroni penguin Eudyptes chrysolophus, snow petrel Pagodroma nivea, Cape pigeon Daption capense, southern fulmar Fulmarus glacialoides, south polar skua Catharacta maccormicki and brown skua Catharacta lonnbergi. The birds were taken in central parts of Vestjella in Dronning Maud Land in February 1977 and at Bouvetøya in the South Atlantic in February 1977 and January 1979. Low levels of DDE, PCB and HCB were found in the two species of penguins, snow petrel, Cape pigeon and southern fulmar, while significantly higher levels were found in south polar and brown skua. The lowest mercury levels were found in the two penguin species and snow petrel. Cape pigeon, southern fulmar and south polar skua form an intermediate group, while the highest mercury levels were found in brown skua. It is assumed that there is a connection between the present findings and the migration pattern of the different birds. The results seem to be in agreement with previous investigations.
Keywords: Bouvetøya; Dronning Maud Land; forurensning; fugler; miljøgifter; ornitologi; økologi